The Effect Of Word Of Mouth On Brand Image Of A Popular Indonesian Donut Brand - Mahir Pradana (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
A Brand must innovate to create a positive impression of consumers. When a consumer feels happy and satisfied with a product, the emotional impact will encourage loyalty and positive word of mouth will increase. The purpose of this research is to know how big influence of word of mouth to brand image of J.CO Donuts & Coffee. The independent variable (X) in this research is word of mouth and the dependent variable (Y) is brand image. This research uses quantitative method with descriptive and causal research type. This research was conducted on 75 respondents and used simple linear regression analysis and data processing using SPSS version 21. Based on the results of hypothesis testing, word of mouth has an influence on brand image J.CO. The results of determination coefficient word of mouth influence to brand image by 46,7%. Keywords: brand image, word of mouth, marketing, business administration